Empowering Sustainable Software Engineering Education with Artificial Intelligence and Immersive Technology - Saputra, Dafid; Tsaqif, Farhan Fadlurohman; Ariana, Aurora Luna (IC-ITECHS, 2024)
This research investigates the impact of integrating artificial intelligence (AI) and immersive technologies, such as virtual reality (VR) and augmented reality (AR), in software engineering education to promote continuous and adaptive learning. The purpose of this study was to explore how these technologies increase student engagement, personalize the learning experience, and enhance practical skills essential in software development. A mixed methods approach was used, combining a quantitative survey with qualitative interviews of 20 students and 5 educators actively engaged in AI and VR powered courses. Findings revealed that AI-based adaptive learning systems encourage personalized feedback and help address individual knowledge gaps, leading to increased engagement and retention. VR based simulations enable hands-on learning, which significantly improves skill acquisition in coding, debugging, and system analysis. Despite these benefits, challenges such as high costs, data privacy concerns, and limited infrastructure remain a barrier to widespread implementation. This study contributes original insights by identifying strategies to mitigate these challenges, including gradual adoption of technology, cloud-based solutions to reduce costs, prioritizing data security, and continuous educator training. The findings underscore the transformative potential of AI and immersive technologies in creating sustainable, accessible and adaptive learning environments and equipping students with the skills needed for the innovation driven software industry.